Empowering hope? : Jürgen Moltmann’s eschatological challenge to ecclesiological responses in the Zimbabwean context of poverty - Banda, Collium (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.